1978
DOI: 10.1007/bf00238708
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamically induced intraspecific aggressive behaviour in the rat

Abstract: Summary.The effects of electrical stimulation of the lateral hypothalamus (LH) of rats on intraspecific aggressive behaviour were studied. In order to investigate the specificity of the stimulation effects, each experimental animal was stimulated in a number of different social situations.Stimulation of the LH in the presence of a subordinate male increased the amount of time spent on aggressive behaviour patterns and locomotion. In the presence of a dominant male, however, the stimulated animal never initiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 21 publications
2
39
0
1
Order By: Relevance
“…* Compared with the correspondent group injected saline into DRN+MRN + Compared with the correspondent group injected 5 ,7-DHT into DRN+MRN Previous electrical stimulation studies have shown that the LHA is involved in aggressive behavior including muricide [5,9,15]. In the present study, the depression of serotonergic innervation in the LHA by 5,7-DHT and the reinnervation of serotonergic fibers in the LHA by raphe transplant directly demonstrate the serotonergic inhibitory role in the hypothalamic aggressive area.…”
Section: Experiments 2 (Exp 2)supporting
confidence: 53%
“…* Compared with the correspondent group injected saline into DRN+MRN + Compared with the correspondent group injected 5 ,7-DHT into DRN+MRN Previous electrical stimulation studies have shown that the LHA is involved in aggressive behavior including muricide [5,9,15]. In the present study, the depression of serotonergic innervation in the LHA by 5,7-DHT and the reinnervation of serotonergic fibers in the LHA by raphe transplant directly demonstrate the serotonergic inhibitory role in the hypothalamic aggressive area.…”
Section: Experiments 2 (Exp 2)supporting
confidence: 53%
“…We stimulate at the same hypothalamic site as Koolhaas [1978], although the test situation is slightly different. The wound pattern is puzzling.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest lab-based experiments focused on violent 'rage' behaviors in cats following neuro-physiological manipulations in the brain (Bard 1929;Kaada 1966). Several rodent models of violence were developed using lesions to pre-frontal cortical areas, models of Alzheimer's disease, epilepsy and electric shock models as summarized by Haller and Kruk (2006).…”
Section: Introductionmentioning
confidence: 99%